Beverage temperature, muscle activation and fatigue at elevated core body temperatrues - Burdon, C.; Schmidt, C.; Johnson, N.; Chapman, P.; O`Connor, H. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Cold receptor stimulation (through the use of ice slushy, menthol or cold neck collar) has recently been shown to elicit performance benefits during exercise tests in the heat [1, 2, 3]. However the contribution of peripheral and central fatigue reduction to this benefit is unclear. This study aimed to measure the effect of ice slushy versus thermoneutral beverage ingestion on maximal voluntary isometric contraction (MVIC) performance using active and inactive muscles and to measure peripheral and central fatigue at elevated core body temperatures. Method: Eight active participants (5M, 3F) performed three 45s MVICs of the elbow flexors and knee extensors in a reclined position (hips, knees & elbow at 90°) at ~37.5°C, 38.5°C and 39.5°C. Two carbon rubber electrodes were placed over the quadriceps and biceps brachii for percutaneous electrical muscle stimulation 5s before and at 15, 30 and 44s during the MVIC. To increase rectal temperature (Tr) participants cycled in 40°C and 50% relative humidity at 60% Work Max. Immediately prior to each MVIC, participants consumed 50g of ice slushy (-1°C, ICE) or thermoneutral drink (38°C, CON) made from 7.4% carbohydrate beverage. Participants consumed water (19°C) during exercise to maintain body mass. Maximal force production (Fmax) was established at a familiarisation trial using 3s MVICs. Results: Participants cycled for 22±5 and 20±7 min to reach 38.5°C and 39.5°C respectively. Weight change was minimal (~400g) but similar between ICE and CON (p=0.24). Quadriceps mean force decreased from 302±180N to 232±151N at 39.5°C (p<0.001). Quadriceps %Fmax decreased at high Tr (14.6±13.1%, p=0.05). Quadriceps peripheral fatigue increased by 4.0±7.6% (p=0.02) and central fatigue increased by 10.6±11.7% (p=0.06) when Tr was elevated to 39.5°C. Biceps mean force decreased from 179±67N to 148±65N at 39.5°C (p<0.001). Peripheral and central fatigue were not significantly increased at 39.5°C (6.9±8.3% p=0.92 & 1.9±22.3% p=0.17 respectively). No variable was significantly different between ICE and CON trials. Discussion: The MVIC caused significant peripheral and central fatigue and mean force output decreased with elevated Tr for both muscle groups. However, only the active (quadriceps) (not inactive biceps) showed decreased Fmax when Tr was elevated. Therefore, increases in peripheral and central fatigue with elevated Tr was observed only with the active muscle group. Ice slushy ingestion failed to ameliorate the possibly overwhelming effect of heat on central fatigue and muscle force production.